The Role of Inclusive Education in Providing The Activity of Students with Disabilities - Kobilova Shakhnoza Khudoyshukurovna; Abdurakhimova Durdona; Ferangiz Safarova; Bobohonova Madina (Web of Journals Publishing, 2023)
The article covers the issues of organizing inclusive education in the conditions of the innovative cluster of pedagogical education, creating the necessary conditions for children with disabilities in a general educational institution, preventing discriminatory problems, and determining the social and psychological environment.
Keywords: pedagogical, inclusive, disabled student, education and training, model, cluster, activity, quality, efficiency, perspective, pedagogical process.